2020
DOI: 10.1371/journal.pone.0240842
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of knowledge on sexually transmitted infections among students in public higher education institutions in Melaka state, Malaysia

Abstract: Introduction The increasing trend of sexually transmitted infections (STIs) among the young population is a significant public health problem. This study aimed to determine the level of knowledge on STIs among students in higher education institutions and its predicting factors, in Melaka. Methodology A cross-sectional study was conducted among 600 students from higher education institutions in Melaka aged between 18 to 30 years old. Multistage sampling of the instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
5
9
1
1
Order By: Relevance
“…Participants who had tertiary education were three times more likely to have a higher knowledge score compared with the participants who had primary education. Consistent with our findings is a study which was conducted in Melaka Malasyia; they found that participants who were studying in a degree program were two times more likely to be knowledgeable about STIs than the one who were not (25) Further this study revealed that sexual behaviour of the study participants in terms of sex with whom, bisexual men had higher odds of knowledge about STIs compared to gay men. These findings are contrary to (26,27) who reported that bisexual men had limited availability of culturally sensitive education materials or health information that is specifically targeted to their needs.…”
Section: Stissupporting
confidence: 91%
“…Participants who had tertiary education were three times more likely to have a higher knowledge score compared with the participants who had primary education. Consistent with our findings is a study which was conducted in Melaka Malasyia; they found that participants who were studying in a degree program were two times more likely to be knowledgeable about STIs than the one who were not (25) Further this study revealed that sexual behaviour of the study participants in terms of sex with whom, bisexual men had higher odds of knowledge about STIs compared to gay men. These findings are contrary to (26,27) who reported that bisexual men had limited availability of culturally sensitive education materials or health information that is specifically targeted to their needs.…”
Section: Stissupporting
confidence: 91%
“…The current study revealed that overall knowledge was moderate to high, with around three-quarters of respondents answering more than half the questions correctly; this is higher than the overall knowledge reported in other studies from Kufa in south Iraq ( 18 ), Iran ( 9 ), and Saudi Arabia ( 11 ) and comparable to results from Malaysia ( 20 , 24 ). In this study, knowledge about STIs was not affected by gender.…”
Section: Discussioncontrasting
confidence: 75%
“…As a result, many adolescents have no knowledge or are misinformed about issues relating to sex. Sex education is essential in reducing unwanted pregnancies and teenagers ought to be properly informed about issues relating to sexual activities [ 20 , 21 ]. Although the majority of the study participants in this study opined that there is a need for increased sex education among high school students as a means of preventing unwanted pregnancy, however most of them were not in support of condoms handout in schools because they believe it could increase promiscuity among teenagers.…”
Section: Discussionmentioning
confidence: 99%